Ms. McCaw learns to draw - Zemach, Kaethe (Arthur A. Levine Books, 2008)
Dudley Ellington struggles to learn anything at school, but when his very patient teacher, Mrs. McGraw, is unable to draw a face on the board, he helps her figure out how to do it.